Assessment of malnutrition in patients with liver cirrhosis using protein calorie malnutrition (PCM) score verses bio-electrical impedance analysis (BIA) - Parkash, Om (BMC Res Notes, 2018)
OBJECTIVE: Malnutrition is a common problem in patients with liver cirrhosis and tools for nutritional assessment are under debate. We conducted this study to assess prevalence of malnutrition in cirrhotic patients using PCM score and BIA. Additionally we compared BIA to PCM score for detecting malnutrition in this patient population. RESULTS: This was a cross sectional study conducted in two tertiary care hospitals of Karachi Pakistan on adults with liver cirrhosis. Malnutrition was assessed by PCM score using anthropometric measurements and biological specimens and (ii) Body cell mass was assessed using BIA. Malnutrition as estimated by the PCM score was present in 122 (73%) of patients in which most patients had mild malnutrition (n = 72 (45%)), followed by 34 (21%) with moderate malnutrition and 3 (1.9%) with severe malnutrition. Malnutrition according to BIA estimated through body cell mass could detect it in 98 (61%) of patients. There was optimal correlation of PCM score with body call mass (Pearson correlation coefficient = 0.3 (p value 0.001)). We conclude that majority of the patients with liver cirrhosis had malnutrition as determined by PCM score. BIA underscored the malnutrition in this patient population.